DUPONT ANALYSIS - A COMPREHENSIVE MEASURE OF RETURN ON EQUITY FOR BANKS - Ashiralieva, Gayratjon kizi (THE INNOVATION ECONOMY, 2026)
Being a strategic approach, the DuPont model serves as an all-encompassing technique to assessing financial performance and management efficiency. This study evaluates the financial performance of JSICB Ipak Yuli for the years 2016 to 2023 using the DuPont analysis that splits ROE into net profit margin, total asset turnover, and equity multiplier. This approach, unlike others, enables a better granular understanding of drivers behind ROE. The results show that a decline by half in profit margin was the most important reason behind the drop in ROE in 2020, meanwhile the increase in efficiency of assets contributed to a rise in total asset turnover. Moreover, the decrease in equity multiplier indicates that there was less reliance on debt financing in the later years. Though there was a decrease in ROE in 2020, the bank was able to recover in a short time due to internally generated profitability and effective cost control. However, it is not without faults such as the reliance on outdated financial information, failing to consider non-financial factors like regulatory changes or environmental elements. Nonetheless, the study shows that DuPont analysis is efficient at revealing performance outcomes and defining performance drivers related to ROE trends in banking.